2006
DOI: 10.1007/s00296-006-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of genotypes at the MICA gene triplet repeat polymorphisms and MEFV mutations to amyloidosis and course of the disease in the patients with familial Mediterranean fever

Abstract: Though the effects of the MEFV genotypes seem clear, there are definitely other modifying factors or genes on the development of amyloidosis and on the course of the disease. For example, some MICA alleles have a protective effect on the prognostic factors in FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…The distributions of genotypes were similar to the Turkish population as reported in the literature, [5,6] and abdominal pain was the most frequent symptom of patients and supports previous studies. [1] This was true for all MEFV genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…The distributions of genotypes were similar to the Turkish population as reported in the literature, [5,6] and abdominal pain was the most frequent symptom of patients and supports previous studies. [1] This was true for all MEFV genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…51 The effects of the major histocompatibility complex class I chain-related gene A (MICA) on the course of FMF have been studied, and no MICA allele was found to have any independent risk factor effect, 52 although one study suggested that the A5 allele had a protective effect against the development of amyloidosis in a subgroup of p.Met694Val homozygotes. 53 Another study found that the impact of p.Met694Val homozygosity on the age at disease onset was aggravated if patients also inherited MICA-A9, whereas the frequency of attacks was found to be dramatically reduced in patients with MICA-A4. The authors commented that these results clarify, at least partly, the inconsistent phenotype-MEFV correlation in FMF.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Some of these alleles differ in their ability to bind to the NKG2D receptor (Steinle et al, 2001). Expression of certain alleles might contribute to inter-individual differences in susceptibility to certain diseases (Bravo et al, 2007;Turkcapar et al, 2007).…”
Section: Nkg2d Ligandsmentioning
confidence: 99%